Teaching Mathematics Through Online at the University Level: An Ethnographic Inquiry - Dawadi, Shiva Datta (The Educator Journal, 2023)
Teaching mathematics at the university level expects a more complex form of algorithmic and theoretical exploration which sometimes could not be delivered as enough as the curriculum demands. In this context, this study primarily focused on exploring the opportunities and challenges of online classes while teaching-learning mathematics at the university level. It is an ethnographic study in which three students and a teacher who had a long experience in online teaching-learning practices were taken as the key respondents. The key informants were requested for writing the reflection about their experiences of learning mathematics through online mode. And, the responses of the students were analyzed and presented in different themes. Based on the responses of the key respondent students, poor networking, unavoidable disturbance, teacher’s artificial pretending, negligence of the teachers, and less ICT-friendly curriculum & teachers were found as the major challenges for the online class. From the perspective of teachers' preparing documents for teaching, students’ negligence, ICT being used only as a means of sharing, taking more time to complete the course, less interactive class, and evaluating the students were found as the major challenges. However, online education provided the teachers and student both with a friend in crisis, sitting home reaching school, reducing unnecessary expenditures, and utilizing video records of the classes. Similarly, for teachers; providing opportunities for professional development, web browsing, any time anywhere teaching-learning, and developing the skills for designing different online evaluation tools have been observed as the major opportunities. Based on these conclusions, even having many challenges of using ICT in teaching university mathematics, its appropriate use leads for the deeper and wider understanding of mathematical contents.